Simple additive weighting for online platform evaluations in small business - Niar Astaginy; Moh. Gifari Sono; Sri Purwati; Tanti Widia Nurdiani; Ghalib Suprianto (Institute of Computer Science (IOCS), 2023)
Choosing the appropriate online selling platform as a small or medium-sized firm (SME) can help grow sales and expand customer base. Using decision-making approaches with the Simple Additive Weighting (SAW) method, you can select the greatest option among multiple alternatives while selecting the best sales platform. This research aims to assist MSMEs in evaluating and assessing online sales platforms based on the assessment criteria of Average transactions (C1), Unsuccessful transactions (C2), Transaction time (C3), Ease of use of the application (C4), Application errors (C5), and Satisfaction in usage features (C6). The results indicated that alternative A4, Instagram, was the greatest alternative online sales platform, followed by alternative A2, Go Food, as the second-ranking alternative, alternative A3, Grab Food, as the third-ranking alternative, and alternative A1, WhatsApp, as the fourth-ranking alternative. Analysis of the final results can be explained by the tendency of the most prioritized criteria with high criteria weight values, namely the average transaction criteria (C1), ease of use (C4), and application user feature satisfaction (C6), to influence the final results of alternative ranking; the final results of ranking can certainly serve as an alternative option for MSME decisions regarding the selection of online sales platforms.